THE INFLUENCE OF PRICE EARNING RATIO (PER), EARNING PER SHARE (EPS), PRICE TO BOOK VALUE (PBV) ON STOCK PRICES AND FIRM SIZE AS MEDIATORS IN FOOD AND BEVERAGE SUB-SECTOR MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2015-2020 - Jesika Sihaloho; Asep Rochyadi PS (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to analyze or find out the influence of 1. Price Earning Ratio against the share price of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2020, 2. Earning Per Share against the share price of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2020, 3. Price to Book Value against the share price of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2020, 4. Price Earning Ratio (PER) to the stock price with Firm Size as a moderator variable in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2020, 5. Earning Per Share (EPS) against the share price with Firm Size as a moderator variable on food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2020, 6. Price to Book Value (PBV) against the stock price with Firm Size as a moderator variable in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2020. The population in this study was 32 companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2015-2020. Sampling used purposive sampling methods and researchers obtained samples as many as 17 companies. Data collection techniques that researchers do by means of documentation studies and literature studies. And the data analysis techniques that researchers use are Descriptive Statistics, Classical Assumption Test, Analysis Apriori Multiple Reggression, and Moderated Regression Analysis. The results showed that 1. Price Earning Ratio (PER) has no effect on stock price, 2. Earnings Per Share (EPS) has a positive and significant effect on the stock price, 3. Price to Book Value (PBV) has a positive and significant effect on the stock price, 4. Price Earning Ratio (PER) to firm size moderated stock prices has no effect, 5. Earnings Per Share (EPS) against firm size moderated stock prices have a significant effect, 6. Price to Book Value (PBV) against the moderated stock price of Firm Size has a significant effect. Keywords: Stock Price, Price Earning Ratio (PER), Earnings Per Share (EPS), Price to Book Value (PBV), Firm Size.